Colorimetric Determination of Al(III) Based on the Aggregation of Gold Nanoparticles Functionalized with Novel 4-Benzoyl Pyrazolone Derivative - Abubaker M.; Che Wan Zanariah Che Wan Ngah; Ahmad M.; Kuswandi B. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS